2010
DOI: 10.1186/1472-6874-10-31
|View full text |Cite
|
Sign up to set email alerts
|

Sexual coercion of married women in Nepal

Abstract: BackgroundSexual coercion is an important public health issue due to its negative association with social and health outcomes. The paper aims to examine the prevalence of sexual coercion perpetrated by husbands on their wives in Nepal and to identify the characteristics associated with this phenomenon.MethodsThe data used in this paper comes from a cross-sectional survey on "Domestic Violence in Nepal" carried out in 2009. A total of 1,536 married women were interviewed and associations between sexual coercion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 38 publications
6
34
2
3
Order By: Relevance
“…This is in accordance with earlier studies conducted in rural Nepal [25], [37]. Women’s acceptance of wife beating did not predict violence from husbands, though there was no significant difference in acceptance of wife beating between couples.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with earlier studies conducted in rural Nepal [25], [37]. Women’s acceptance of wife beating did not predict violence from husbands, though there was no significant difference in acceptance of wife beating between couples.…”
Section: Discussionsupporting
confidence: 92%
“…A cross sectional study conducted among 1,296 rural married women of 15–24 years of age representing four major ethnic groups of four districts (Dolkha, Sindhupalchowk, Dang, and Kapilbastu) in Nepal reported that 46% had experienced sexual violence from husbands at some point of life and 31% experienced sexual violence in the last 12 months 3. Another cross sectional study among 1,536 reproductive age married women of four districts (Achham, Gulmi, Rupendehi, and Ilam) reported that 58% had experienced sexual violence from their husbands at some point in their lives 4. Similarly, another study interviewed 791 married women of reproductive age from rural parts of six districts (Dadeldhura, Nawalparasi, Makwanpur, Siraha, Sindhupalchowk, and Sankhuwashava) of Nepal revealed that 16.6% experienced sexual violence from intimate partners at any point of life and 7.1% had sexual violence from an intimate partner in the last 12 months 5.…”
Section: Introductionmentioning
confidence: 99%
“…Evlilik içi cinsel saldırı tanısı çok güç olan önemli bir halk sağlığı sorunudur (12)(13)(14)(15). Dünya'da evli kadınların % 15-71'inin eşleri tarafından tecavüze uğradıkları bildirilmiştir (16).…”
Section: Discussionunclassified
“…Dünya'da evli kadınların % 15-71'inin eşleri tarafından tecavüze uğradıkları bildirilmiştir (16). Nepal'de yapılan bir çalışmada her 5 evli kadından 3'ünün eşleri tarafından cinsel saldırıya maruz kaldığı belirlenmiştir (13). Etiyopya'da bu oranın % 46 olduğu bildirilmiştir (17).…”
Section: Discussionunclassified
See 1 more Smart Citation